Eating habits of pregnant brazilian women: An integrative review of the literature - De Gomes, Caroline [UNESP]; Vasconcelos, Letícia Garcia [UNESP]; De Campos Cintra, Renata Maria Galvão [UNESP]; Domingues, Domingues [UNESP]; De Barros Leite, Maria Antonieta [UNESP] (FapUNIFESP (SciELO), 2019)
The eating habits of pregnant women are influenced by several factors, and it is essential to understand them in order to establish nutritional interventions in prenatal care. The objective of this integrative review was to analyze the bibliographic production on the eating habits of pregnant Brazilian women. A search was conducted in the Biblioteca Virtual em Saúde (BVS), PubMed, Scopus, Web of Science and Scientific Electronic Library Online databases (SciELO) using the following key words: “Gestantes” or “Grávidas” and “Hábitos Alimentares” in Portuguese, and “Pregnant women” and “Eating habits” and “Brazil” in English. After the adoption of inclusion and exclusion criteria, 18 studies were analyzed. Some studies targeted specific populations such as adolescents or non-obese pregnant women. The Food Frequency Questionnaire was the instrument most often used to investigate food consumption among pregnant women. The majority of the studies revealed that the diet of pregnant women needs improvement, especially due to the low consumption of fruit, greens and vegetables, and the high consumption of sugar, sweets and fats. Most studies concluded and reinforced the importance and need for nutritional education by prenatal professionals. More studies are needed to better understand these eating habits.
Hábitos alimentares das gestantes brasileiras: Revisão integrativa da literatura
Keywords: Eating habits; Pregnant women; Prenatal Nutrition